Arginase and vascular aging - Santhanam, Lakshmi (American Physiological Society, 2008)
Vascular and associated ventricular stiffness is one of the hallmarks of the aging cardiovascular system. Both an increase in reactive oxygen species production and a decrease in nitric oxide (NO) bioavailability contribute to the endothelial dysfunction that underlies this vascular stiffness, independent of other age-related vascular pathologies such as atherosclerosis. The activation/upregulation of arginase appears to be an important contributor to age-related endothelial dysfunction by a mechanism that involves substrate (l-arginine) limitation for NO synthase (NOS) 3 and therefore NO synthesis. Not only does this lead to impaired NO production but also it contributes to the enhanced production of reactive oxygen species by NOS. Although arginase abundance is increased in vascular aging models, it appears that posttranslational modification by S-nitrosylation of the enzyme enhances its activity as well. The S-nitrosylation is mediated by the induction of NOS2 in the endothelium. Furthermore, arginase activation contributes to aging-related vascular changes by mechanisms that are not directly related to changes in NO signaling, including polyamine-dependent vascular smooth muscle proliferation and collagen synthesis. Taken together, arginase may represent an as yet elusive target for the modification of age-related vascular and ventricular stiffness contributing to cardiovascular morbidity and mortality.